Implementation of the use of textbooks with the context of socio scientific issues on climate change materials and its impact on life to improve students' scientific literacy - Asep Saefullah; Yudi Guntara; Diana Ayu Rostikawati (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2021)
The purpose of this study was to determine the effect of implementing the use of teaching materials in the context of Socio-Scientific Issues (SSI) on students' scientific literacy on climate change material and its impact on life. The research method used is a weak experiment with a one-group pretest-posttest design. The number of samples used is 60 students who are contracting Earth and Space Sciences (IPBA) courses. The research instrument used is a multiple-choice scientific literacy test instrument. The results showed that the use of teaching materials with the SSI context affected students' scientific literacy. This can be seen from the effects of statistical tests, which showed the arithmetic significance value (0.002) < 0.05. The use of teaching materials in the SSI context can also improve students' scientific literacy, which can be seen in the n-gain value of 0.54, which is in the medium category.